Bioinspired superhydrophobic patterned surfaces as chips for high-throughput analysis of biomaterials viscoelastic properties - Oliveira, Mariana B. (2012)
Tissue-constituent cells are usually anchorage-dependent cells. Their viability is compromised when they are in a fluid suspension. The adhesion of these cells in the body occurs in solid elastic tissues. Mechanical properties of biomaterials were reported to have a role in modulating cells response, affecting their function and structure, as well as the direction of differentiation [1]. Cells like neurons, muscle cells, mesenchymal stem cells are examples of cells previously reported to be dependent on substrates stiffness. It is well known that interactions occurring in the area of tissue engineering and regeneration are not easily predictable. As such, we previously developed arrays of wettable spots in polystyrene superhydrophobic surfaces in order to use these structures as high-throughput platforms for biomaterials development. We patterned biomaterials precursors in the wettable spots, keeping them confined in such regions by the wettability contrast caused by the superhydrophobic surroundings. The method was used to study several cells-biomaterials interactions in 3D milieu. We studied the effect of distinct combinations of biomaterials in encapsulated cells [2], as well as cells-porous scaffolds interactions [3]. Adapted chips based on the same concept were also used to develop an on-chip drug-release quantification device [4]. By using the same type of chips developed for cells-biomaterials interactions studies, we aimed to adapt the system for the rapid study of miniaturized biomaterials viscoelastic properties. Most living tissues show a viscoelastic behavior, i.e., besides showing a particular stiffness, they have the ability to dissipate energy during cyclic stimulation. We used superhydrophobic chips to pattern miniaturized hydrogels, and adapted a mechanical dynamic analyzer (DMA) so on-chip viscoelastic properties of those materials could be assessed under physiological-like conditions. For the proof-of-concept we performed a three-factor combinatorial study targeting bone tissue engineering applications. A system consisting of distinct combinations of polymeric matrix concentration, crosslinking degree and addition of biomineralizable bioglass nanoparticles was systematically studied. We believe this system will facilitate the on-chip rapid study of miniaturized biomaterials for the future discovery of the role of the viscoelastic properties of tissues and materials in cell response. [1] A. J. Engler, S. Sen, H. L. Sweeney, D. E. Discher, Cell 2006, 126, 677. [2] C. L. Salgado, M. B. Oliveira, J. F. Mano, Integrative Biology, 2012, 4, 318. [3] M. B. Oliveira, C. L. Salgado, W. Song, J. F. Mano, Small 2013, 9, 768. [4] M. B. Oliveira, J. F. Mano, Analytical Chemistry, 2013, 4, 2391.